1995
DOI: 10.1097/00000658-199506000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Management of Blunt Hepatic Trauma Is the Treatment of Choice for Hemodynamically Stable Patients Results of a Prospective Trial

Abstract: Nonoperative management is safe for hemodynamically stable patients with blunt hepatic injury, regardless of injury severity. There are fewer abdominal complications and less transfusions when compared with a matched cohort of operated patients. Based on admission characteristics or CT scan, it is not possible to predict failures; therefore, intensive care unit monitoring is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
286
2
23

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(323 citation statements)
references
References 23 publications
12
286
2
23
Order By: Relevance
“…The abdomen is often injured by both penetrating and blunt trauma and the liver, due to its size and anatomical location, is frequently affected [1][2][3] . Hepatic trauma corresponds to approximately 5% of admissions to emergency rooms 2,4 . In recent years, the diagnosis and treatment of hepatic trauma has evolved with the use of computerized tomography (CT), and the likelihood of non-operative management for selected hemodynamically stable patients has become a reality in many trauma centers worldwide.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…The abdomen is often injured by both penetrating and blunt trauma and the liver, due to its size and anatomical location, is frequently affected [1][2][3] . Hepatic trauma corresponds to approximately 5% of admissions to emergency rooms 2,4 . In recent years, the diagnosis and treatment of hepatic trauma has evolved with the use of computerized tomography (CT), and the likelihood of non-operative management for selected hemodynamically stable patients has become a reality in many trauma centers worldwide.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…The incidence of liver injury in our study is higher as compared to reported incidence of liver injury in literature. Croce et al [2] reported 5 % incidence of liver injury while Malhotra et al [3] had reported 4.6 % incidence of liver injury.…”
Section: Discussionmentioning
confidence: 98%
“…Recent series of NOM has demonstrated that it is safe and effective in selected patients with both blunt and penetrating abdominal trauma with variable success rate ranging between 83 and 97 % [2][3][4]7]. Petrowsky et al [4] had shown 96 % success rate of NOM with 2.2 % liver-specific failure rate of NOM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bolesnici sa povredama jetre čine oko 5% svih politraumatizovanih [4], a oko 35% ovih povreda je prisutno u abdominalnoj traumi. Na povrede jetre treba pomisliti kod svih bolesnika sa tupom ili penetrantnom torakoabdominalnom traumom, posebno kod onih u stanju šoka sa povredama na desnoj strani tijela.…”
Section: Uvodunclassified